Physicochemical and Sensory Characteristics of Kemang (Mangifera Caesia) and Machete Gourd (Cucurbita Moschata Durch) Fruit Leather - Mir'atu Saa'dia Septiani; Rosy Hutami; Titi Rohmayanti (Universitas Djuanda, 2022)
Kemang fruit is a seasonal fruit that can only be enjoyed in certain seasons and has yet to be used optimally. Processing Kemang fruit into fruit leather is one of the efforts to optimize the consumption of Kemang fruit. This study aims to determine Kemang and machete gourd fruit leather's physical, chemical, and sensory qualities. It used a completely randomized design (CRD) in which the proportion of Kemang and machete gourd puree was the factor. It consisted of three treatment levels ( 2:3, 1:1, 3:2). Data analysis used ANOVA and DMRT as the further test with a 95% confidence level. The results showed the proportion of Kemang and machete gourd puree affected physical characteristics (strong), chemical characteristics (water content and crude fiber content), and sensory quality tests (taste, color, texture). The selected fruit leather was fruit leather with a ratio of Kemang and machete gourd A1 (2:3), which has an average value of physical and chemical characteristics, namely tensile strength of 0.06 N/mm2, elongation of 9.484%, moisture content of 26.48 %, water activity (Aw) 0.78, fiber content 4.34%, and crude level (pH) 4.2. The average value of the sensory quality test, namely taste 4,940, color 7,200, aroma 5.8, texture 4.5, and the hedonic test, namely taste 6.3, color 7.0, aroma 6.5, texture 6.6, and overall 7.2. It can be concluded that the less proportion of Kemang puree compared to the machete gourd puree (2:3) will give the best characteristics of fruit leather.